Plasma trimethylamine‐N‐oxide following supplementation with vitamin D or D plus B vitamins. Issue 2 (10th October 2016) - Obeid, Rima; Awwad, Hussain M.; Kirsch, Susanne H.; Waldura, Christiane; Herrmann, Wolfgang; Graeber, Stefan; Geisel, Juergen
Abstract : In this 1‐year trial of vitamin D or D plus B9, B12, and B6, B vitamins lowers plasma homocysteine and increased betaine. Vitamin D shows a choline sparing effect in both arms. The combination of vitamins D and B lowers plasma TMAO compared to vitamin D alone. The effect of vitamin D + B on choline may mediate their effect on TMAO. Abstract : Scope: We compared the effect of supplementation with vitamin D + B or vitamin D on plasma trimethylamine N‐oxide (TMAO) and choline metabolites. Methods and results: This is a randomized single‐blinded nonplacebo‐controlled study. Twenty‐seven participants received 1200 IU vitamin D3 and 800 mg calcium, and 25 participants received additionally 0.5 mg folic acid, 50 mg B6, and 0.5 mg B12 for 1 year. Plasma homocysteine (Hcy), TMAO, and choline metabolites were measured at baseline and 12 months later. TMAO declined in the vitamin D arm by 0.5 versus 2.8 μmol/L in the D + B arm ( p = 0.005). Hcy decreased and betaine increased in the D + B compared to the D arm. Within‐subject levels of plasma choline and dimethylglycine and urine betaine increased in both arms and changes did not differ between the arms. TMAO reduction was predicted by higher baseline TMAO and lowering Hcy in stepwise regression analysis. The test–retest variations of TMAO were greater in the D + B arm compared to vitamin D arm. Conclusion: B vitamins plus vitamin D lowered plasma fasting TMAO compared to vitamin D. Vitamin D caused alterations in choline metabolism, which may reflect the metabolic flexibility of C1‐metabolism. The molecular mechanisms and health implications of these changes are currently unknown.